Assessing the Clinical Features and Blood Biochemistries of Acute Organophosphorus Chemical Warfare Agents in Iranian Veterans - Agin, Khosrow; Mostafazadeh, Babak (International journal of medical toxicology and forensic medicine, 2021)
Background: Nerve Agents (NAs) are a chemical weapons, and their use is prohibited. They were used for numerous-times in the warfare of Iraq against Iran. The present study aimed to assess the clinical features and laboratory findings of the acute poisoning manifestations of organophosphorus chemical warfare agents (NAs) in Iranian veterans early after exposure. Methods: A total of 25 male NAs-exposed cases were enrolled in the present study. We used the medical records of early combat in 1990 for data collection. The data of the exposed-victims were unavailable for a long time. Clinical features were evaluated and fasting blood glucose, sodium, potassium, insulin level, and protein electrophoresis were measured on the first day of exposure. Results: Potassium, sodium, fasting blood glucose, and protein electrophoresis were abnormally noticeable on the first day post-exposure. The clinical features of the studied cases were manifested in the muscarinic and nicotinic systems, and Central Nervous Systems (CNS). Miosis, cramp, restlessness, and respiratory symptoms were dominant features in the study subjects. Conclusion: The investigated exposed-victims of NAs indicated hypokalemia, hyperkalemia, hypoglycemia, normal insulin levels, and abnormal protein electrophoresis. The clinical features of the cholinergic crisis were markedly significant in three levels of the muscarinic, nicotinic, and CNS manifestations. Our findings suggested that the exposed cases were against a significant dose of NAs.